2019
DOI: 10.1016/j.molmet.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Optimized GIP analogs promote body weight lowering in mice through GIPR agonism not antagonism

Abstract: Objective Structurally-improved GIP analogs were developed to determine precisely whether GIP receptor (GIPR) agonism or antagonism lowers body weight in obese mice. Methods A series of peptide-based GIP analogs, including structurally diverse agonists and a long-acting antagonist, were generated and characterized in vitro using functional assays in cell systems overexpressing human and mouse derived receptors. These analogs were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
147
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 49 publications
16
147
1
2
Order By: Relevance
“…Killion et al [41] provided a preclinical validation of a therapeutic approach to treat obesity with anti-GIPR antibodies. However, there is no agreement on whether GIP receptor agonism or antagonism lowers body weight [42]. Recently published in The Lancet, data from a phase II trial on dual human agonist with an imbalance in favour of GIP agonism showed significantly better efficacy with regard to weight loss than did selective stimulation of GLP-1 receptor [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Killion et al [41] provided a preclinical validation of a therapeutic approach to treat obesity with anti-GIPR antibodies. However, there is no agreement on whether GIP receptor agonism or antagonism lowers body weight [42]. Recently published in The Lancet, data from a phase II trial on dual human agonist with an imbalance in favour of GIP agonism showed significantly better efficacy with regard to weight loss than did selective stimulation of GLP-1 receptor [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have targeted either GIP (Barbosa-Yañez et al, 2019;Boylan et al, 2015) or GIPR (Killion et al, 2018) with antagonist antibodies and have revealed a protective effect against dietinduced body weight gain. Others have used GIPR peptide agonists to show that by chronically infusing either GIP analog (Mroz et al, 2019) or by a dual treatment with a GLP-1 analog (Finan et al, 2013), a decreased weight and metabolic benefits can be achieved. These discrepancies argue that a modulation rather than a complete abolition or chronic activation of GIPR activity is key to a better metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it was reported that GIP overexpression in mice results in improved glucose tolerance with enhanced β‐cell function and resistance to high‐fat diet‐induced obesity, and that chronic activation of GIPR using acylated GIP analog, (d‐Ala(2))GIP[Lys(37)PAL], improves glycemia without excess bodyweight gain in high‐fat diet‐induced obesity in mice. Importantly, the bodyweight reduction by the GIP analog was abolished by pair‐feeding, suggesting that GIP agonist treatment reduces bodyweight mainly due to suppression of food intake. Thus, conflicting results in GIPR‐deficient mice and mice receiving GIP analog might be due to pharmacological levels of the GIP signal in the central nervous system that decrease food intake and overcome the obesogenic effects of GIP at physiological levels in the adipose tissues.…”
Section: List Of Antidiabetic Drugs Targeting Glucagon‐like Peptide‐1mentioning
confidence: 99%